Stability and performance analysis of a single‐stage grid‐connected photovoltaic system using describing function theory. (20th January 2016) - Hejri, Mohammad; Mokhtari, Hossein; Karimi, Soraya; Azizian, Mohammadreza
Summary: Challenging problems in the design and analysis of photovoltaic (PV) systems stem from the nonlinear current–voltage (I–V) characteristics of solar cells. This paper presents an analytical analysis based on a describing function method to investigate the transient and steady‐state characteristics of a three‐phase single‐stage grid‐connected PV system. In this study, the nonlinear I–V characteristic of the PV array is linearized around the operating point. The nonlinear dynamic of the maximum power point tracking controller is divided into two parts of continuous and discrete. For the continuous part, the common small‐signal linearization is applied, while for the discontinuous part, a describing function is derived. Using the proposed technique, the stability and performance characteristics of the closed‐loop system limit cycle as a function of the maximum power point tracking parameters are studied. The accuracy of the predicted limit cycles based on the describing function analysis is investigated by detailed computer simulations of a large‐scale 100 kW three‐phase single‐stage grid‐connected PV system. The proposed analysis is a complement work and mathematical support to the low‐scale experimental observations in the field. It can also serve as a low‐cost systematic approach to regulate PV control system parameters for the stability, robustness and performance evaluation of the PV systems. Copyright © 2016 John Wiley & Sons, Ltd.